2008
DOI: 10.1007/s10517-008-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of bone marrow mesenchymal (stromal) stem cells in experimental ischemic stroke in rats

Abstract: The effects of human mesenchymal stem cells on neurological functions and behavioral reactions of animals and on damaged brain tissue were studied on the model of focal cerebral ischemia in rats. Homing and differentiation of transplanted mesenchymal stem cells were also studied. Significant regression of neurological disorders after cell transplantation was noted, no appreciable shifts were detected by magnetic resonance tomography. Homing of transplanted cells was detected mainly in the zone of focal ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…As stem cells, BMSCs can differentiate into multiple lineages. Previous research has shown that transplantation of BMSCs significantly reduces the impairment of neurologic function after cerebral ischemia [58]. BM-MNCs comprise mainly mesenchymal cells and hematopoietic cells [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stem cells, BMSCs can differentiate into multiple lineages. Previous research has shown that transplantation of BMSCs significantly reduces the impairment of neurologic function after cerebral ischemia [58]. BM-MNCs comprise mainly mesenchymal cells and hematopoietic cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have demonstrated the high therapeutic value of BMSCs for ischemic stroke in animals [58], BMSCs are generally considered more difficult to culture and purify than bone marrow mononuclear cells (BM-MNCs). BM-MNCs comprise mesenchymal and hematopoietic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of MSCs derived from bone marrow [49], Ding et al [41] transplanted approximately 1×10 6 clonally expanded hUC-MSCs into the cortex of middle cerebral artery occlusion (MCAO) rat models and observed significantly improved neurological function as well as considerably increased cortical neuronal activity. The transplanted hUC-MSCs migrated towards the ischemic boundary zone and differentiated into glial, neuronal, doublecortin + , CXCR4 + , and vascular endothelial cells [41].…”
Section: Experimental Application In Cerebral Ischemiamentioning
confidence: 99%
“…The reported sources of mesenchymal stem cells include bone marrow (Skvortsova et al 2008), adipose tissue (Gutierrez-Fernandez et al 2013a), embryo (Liu et al 2009), placenta (Kranz et al 2010), dental pulp and periodontal ligament (Moshaverinia et al 2014;Vasandan et al 2014). Other sources, including palatine tonsil (Janjanin et al, 2008), dermis (Feisst et al 2014), and skeletomuscular system (Aydin et al 2014;Mason et al 2014), have also been reported.…”
Section: Advantages Of Therapeutic Use Of Adipose-derived Mesenchymalmentioning
confidence: 99%